Mortal zin - Schaffer, Diane (Mortal Zin mystery, 2025)
When corporate attorney Noli Cooper visits her godparents' Santa Cruz Mountain winery, she's hoping for a few quiet days to consider her future. But the future will have to wait. The body of her childhood mentor, a crusading social justice lawyer and local hero, is discovered in a rocky ocean cove. The sheriff is quick to call it suicide. Noli knows he's wrong. Teaming up with PI Luz Alvarado, Noli dives into a world where nothing is as it seems. As threats mount and the winery teeters on the brink of ruin, Noli and Luz must navigate a treacherous landscape of greed, revenge, and long-buried secrets. Their investigation weaves through the rich tapestry of California's vineyard history, the mystery of zinfandel grapes, and the haunting legacy of the Vietnam War. With a murderer on the loose, predatory neighbors circling, and Noli's godfather framed for murder, the clock is ticking. Can two fearless women from different worlds unravel the truth before it's too late?